Social Impact Assessment in The Development of A Nickel Smelter in Morowali District - Ahmad Taufik; Deddy T Tikson; Muhammad Yunus (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
This research aims to evaluate the impact of nickel smelter development on the social welfare of the Morowali community. Its urgency lies in the need to understand the social consequences of rapid industrialization, so that mitigation policies and community participation can be formulated more inclusively and sustainably. This research uses a qualitative approach with a phenomenological design and Social Impact Assessment (SIA) to explore the social impacts of nickel smelter development in Morowali. Data were obtained thru interviews, documentation, and observation, and analyzed using Nvivo 12 Plus to identify key themes and develop mitigation recommendations based on the findings. This study shows that while industrialization drives rapid economic growth, it also leads to social impacts, including limited access to basic facilities such as clean water, sanitation, housing, education, and healthcare. Other impacts are seen in public health due to air pollution, increasing social tensions between local workers and foreign labor, and low public participation and protection of vulnerable groups' rights. Overall, the smelter development has not fully considered the principles of sustainable development, as the main focus is still on economic growth without ensuring social welfare, justice, and the protection of community rights. Future policy recommendations include strengthening collaboration between local governments, companies, and communities to improve access to basic facilities, healthcare services, education, and the protection of citizens' rights. Additionally, the sustainable and transparent implementation of the Social Impact Assessment mechanism needs to be carried out so that industrial growth aligns with social welfare and sustainable development.